ARRANGEMENTS OF LAW ENFORCEMENT INVOLVING LAW ENFORCEMENT OFFICERS IN BRIBERY - Bagus Priandy; Eva Achjani Zulfa; Surya Nita (International Journal of Innovative Technologies in Social Science, 2022)
There are still a number of individuals and government bodies in Indonesia that have the capacity to abuse the power that they possess. In government entities, it is possible for KPK investigators to abuse their positions of power. Since the investigators have to make direct contact with the crime or the suspect, it is possible that they will accept bribes or gifts. This study aims to investigate the types of crimes that may be committed by KPK investigators when handling corruption cases, the criminal liability of law enforcement based on the Criminal Acts of Corruption Act, and the efforts made by the government to address the issue of criminal acts of corruption. This article employs qualitative analysis, which entails a detailed description of the processed data in the form of phrases, as the technique of data analysis used in this research (descriptive). In terms of Indonesian criminal law, corruption is governed by Law No. 31 of 1999 and Law No. 20 of 2001 on the Eradication of Corruption Crimes. These rules establish the extent of the punishment for corruption offenders, which includes imprisonment, fines, and the death penalty. In addition, the government aims to seize the profits of illegal acts of corruption via asset recovery through enforcing the Law on the Prevention and Eradication of the Crime of Money Laundering. Regarding law enforcement, the government created the Corruption Eradication Commission (KPK) and the Corruption Court.